Kyoto, Doha et après : enjeux autour des négociations de l’après-Kyoto - Sebastian Weissenberger (VertigO)
Following the climate conferences of Copenhagen and Durban, the international climate politics are at a turning point. On one hand, a continuation of the Kyoto protocol beyond the first commitment period ending in 2012 remains uncertain. On the other hand, a new global climate treaty for the period after 2020 is to be negotiated by 2015. The sharing of the effort will be determined by ethical, pragmatic and political considerations. Ultimately, all countries will have to make compromises if the climate stabilisation goals laid out in Copenhagen are to be achieved. Nevertheless, climate justice considerations need to be taken into account.